2014
DOI: 10.7589/2013-11-296
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Paralytic Shellfish Poisoning in Kittlitz's Murrelet (Brachyramphus brevirostris) Nestlings, Alaska, USA

Abstract: ABSTRACT:Paralytic shellfish poisoning (PSP) is an acute toxic illness in humans resulting from ingestion of shellfish contaminated with a suite of neurotoxins (saxitoxins) produced by marine dinoflagellates, most commonly in the genus Alexandrium. Poisoning also has been sporadically suspected and, less often, documented in marine wildlife, often in association with an outbreak in humans. Kittlitz's Murrelet (Brachyramphus brevirostris) is a small, rare seabird of the Northern Pacific with a declining populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 9 publications
(10 reference statements)
0
14
0
Order By: Relevance
“…However, large die-offs have been rare. Per event, documented mortality has been relatively low in magnitude, ranging from <10 individuals (Shearn-Bochsler et al 2014) up to several thousand individuals in only a few cases (McKernan & Scheffer 1942, Sasner et al 1974. The 2007 MME in Monterey Bay, also a consequence of an A. sanguinea bloom, only resulted iñ 200 carcass recoveries and ~500 live impaired birds, and species-specific encounter rates that were 2 to 24 , with the number of individuals contributing toward that proportion illustrated by dot size.…”
Section: Discussionmentioning
confidence: 99%
“…However, large die-offs have been rare. Per event, documented mortality has been relatively low in magnitude, ranging from <10 individuals (Shearn-Bochsler et al 2014) up to several thousand individuals in only a few cases (McKernan & Scheffer 1942, Sasner et al 1974. The 2007 MME in Monterey Bay, also a consequence of an A. sanguinea bloom, only resulted iñ 200 carcass recoveries and ~500 live impaired birds, and species-specific encounter rates that were 2 to 24 , with the number of individuals contributing toward that proportion illustrated by dot size.…”
Section: Discussionmentioning
confidence: 99%
“…We found 11 nestlings dead in their nests, accounting for 21% of total nest fates from 2008 to 2011. Subsequent analysis of a sample of dead nestlings found in 2011 (N = 5) and 2012 (N = 3) revealed that exposure to saxitoxin, a biotoxin associated with paralytic shellfish poisoning, was a primary cause of chick mortality (Shearn-Bochsler et al 2014). Seven of 52 eggs were abandoned during our study.…”
Section: Resultsmentioning
confidence: 99%
“…Cloacal contents (4 birds) and stomach content samples (2 birds) were sent to the Wildlife Algal-toxins Research and Response Network (WARRN-West) to analyze for harmful algal toxins domoic acid and saxitoxin using an ELISA (Abraxis, Inc.). Remaining birds could not be tested for algal toxins due to insufficient stomach contents for diagnostic analyses, or decomposition state [50].…”
Section: Methodsmentioning
confidence: 99%